A Novel Design for Steerable Instruments Based on Laser-Cut Nitinol. (June 2014) - Dewaele, Frank; Kalmar, Alain F.; De Ryck, Frederic; Lumen, Nicolaas; Williams, Leonie; Baert, Edward; Vereecke, Hugo; Kalala Okito, Jean Pierre; Mabilde, Cyriel; Blanckaert, Bart; Keereman, Vincent; Leybaert, Luc; et al.
Objective . Omnidirectional articulated instruments enhance dexterity. In neurosurgery, for example, the simultaneous use of 2 instruments through the same endoscopic shaft remains a difficult feat. It is, however, very challenging to manufacture steerable instruments of the requisite small diameter. We present a new technique to produce such instruments by means of laser cutting. Only 3 coaxial tubes are used. The middle tube has a cutting pattern that allows the steering forces to be transmitted from the proximal to the distal end. In this way the steering part is concealed in the wall of the tube. Large diameter articulated instruments such as for laparoscopy might benefit from the excellent tip stability provided by the same economical technology. Method . Coaxial nitinol tubes are laser-cut with a Rofin Stent Cutter in a specific pattern. The 3 tubes are assembled by sliding them over one another, forming a single composite tube. In a surgical simulator, the neurosurgical microinstruments and laparoscopic needle drivers were evaluated on surgical convenience. Results . Simultaneous use of 2 neurosurgical instruments (1.5 mm diameter) through the same endoscopic shaft proved to be very intuitive. The tip of the steerable laparoscopic instruments (10 mm diameter) could resist a lateral force of more than 20 N. The angle of motion for either instrument was at least 70° in any direction. Conclusions . A new design for steerable endoscopic instruments is presented. It allows the construction in a range from microinstruments to 10-mm laparoscopic devices with excellent tip stability.